1985
DOI: 10.1056/nejm198507043130104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings in Four Children with Biotinidase Deficiency Detected through a Statewide Neonatal Screening Program

Abstract: Four children with biotinidase deficiency were identified during the first year of a neonatal screening program for this disease in the Commonwealth of Virginia. Two unrelated probands were identified among the 81,243 newborn infants who were screened. In addition, two siblings of one of these infants were found to be affected. Both probands had mild neurologic symptoms at two and four months, respectively, and the two older children had more severe neurologic abnormalities, cutaneous findings, and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 7 publications
0
32
1
1
Order By: Relevance
“…6,7 The first newborn screening for biotinidase deficiency was initiated in Virginia in 1984. 8 The state of Michigan began screening in 1988. However, even though many states have been screening for a relatively long period of time, few studies have been reported that have examined the outcomes of the individuals identified by newborn screening.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The first newborn screening for biotinidase deficiency was initiated in Virginia in 1984. 8 The state of Michigan began screening in 1988. However, even though many states have been screening for a relatively long period of time, few studies have been reported that have examined the outcomes of the individuals identified by newborn screening.…”
Section: Introductionmentioning
confidence: 99%
“…50 Biotinidase deficiency meets many of the criteria for inclusion in state newborn screening programs: there is an inexpensive and reliable screening test, the disorder is associated with high morbidity and mortality if untreated, an easy and effective treatment exists, and the population incidence is comparable to that of other disorders screened. 51 Several studies have shown the cost-effectiveness of screening for both profound and partial biotinidase deficiency. [52][53][54] Currently, all newborn screening programs in the United States and more than 30 other countries screen for biotinidase deficiency, with multiple recent studies suggesting that additional countries are considering incorporation of biotinidase deficiency into their newborn screening programs.…”
Section: Newborn Screening For Biotinidase Deficiencymentioning
confidence: 99%
“…Enzyme activity is either determined using a colorimetric assay, in which biotiniyl-p-aminobenzoate is the substrate, or using a fluorimetric assay, in which biotinyl-6-aminoquinoline is usually the substrate. 15,[60][61][62][63] If an individual is being treated with sulfa medications, false-negative results can occur when using the assay where biotinyl-p-aminobenzoate is the substrate 15 ; fortunately, sulfa medications are contraindicated for biotin concentrations are useful in differentiating among biotin deficiency, biotinidase deficiency, and holocarboxylase synthetase deficiency, but it is important to know the method used for determining the biotin concentration. 2 Only methods that distinguish biotin from biocytin or bound biotin yield reliable estimates of free biotin concentrations.…”
Section: Methodologies and Limitationsmentioning
confidence: 99%